PENDEKATAN KONSTRUKTIVISTIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP ZAINUL HASAN GENGGONG TAHUN 2018 - admin, admin (LP3M UNZAH GENGGONG, 2019)
Abstract Education has a very decisive role for the development and realization of individual self, especially for the development of the Nation and the State. Education is also responsible for guiding and fostering talent and creativity. The weak point of education in Indonesia so far is that the learning process is dominated by a behavioristic approach, namely that students act more as objects and teachers as subjects, so that learning can turn off student learning creativity. right. In this case learning that is considered appropriate is a constructivist approach. Where the learning is done by two parties GurudanSiswayang both act as subjects in learning. The results of this study include, (1) Developing the ability of students to ask questions and find their own questions, so students build knowledge based on their own or individual efforts, the teacher's task is only as a facilitator or mediator. The teacher only gives direction so that students are motivated in learning or gain knowledge, (2) students to develop understanding and understanding of concepts in full (3) students can be responsible (4) teachers give to students and institutions hold training for constructivist approaches of PAI teachers, ( 5) Students' awareness, before entering the class, they must first learn about the material to be learned in class. From the results of this study the researchers gave the following suggestions: (1) before teaching the teacher must understand the learning experience that is more in accordance with the needs of students (2) the teacher's expectation is really directly involved in the course of learning (3) so that further research is carried out using the research design qualitative in order to obtain more in-depth research results. Keywords: Construtivism Approach, Islamic Religious Education Learning